ASSESSMENT OF THE FOREST COVER IN COSTA RICA: AN APPROACH USING CONSERVATION AREAS IN THE YEAR 2000 - Morera-Beita, Carlos (2016)
Over the past years, geography has faced a dizzying development related to environmental concerns facing today’s society. This is facilitated by the development of technological applications, which has expanded the geographical knowledge. Topics addressed within this trend include research on land use, which present detailed information and facilitate the monitoring of ecosystems, which is highly relevant in these days of accelerated climate change. This article analyzes the forest cover in Costa Rica during 2000, using Landsat images. Conservation areas as ecological regions that facilitate the analysis at this level are used in order to identify the local differences of the forest distribution. It is concluded that the country presents a high proportion of the forest cover especially of the low-density one that results from an accelerated process of natural regeneration, especially in some regions. This is related to changes in the economic model that has been oriented to the sector service to the detriment of agro-pastoral activities detriment as well as ecological factors that facilitate regeneration in tropical ecosystems. This research evidenced a reduced area of high-density forest cover by conservation region in comparison to the low-density one. However, the presence of fragments of dense forest with a medium to high surface -which are suitable for ecological conservation, prevails.